LIMA CULTURE IN THE VALLEY UNDER THE CHILLÓN RÍO - Paredes Olvera, Juan (2000)
The purpose of this work is to evaluare data reunited until this moment and, likewise, add new data that could let establish the characteristics of arqueological monuments located in low Chillon river. In the same way, to study the area population pattern and to analize the existent relatio nship among the establishments, enviro nment and the probable production systems. We can determine the type and the constructive materials used, identify the type, the character's establishments of this are.a, define the urban characteristics of the principal sites and propose thesis about the occupation consequences and handle the resources of the study zone.